Solution
Solution
Solution steps
Simplify
Apply the Product Rule:
Simplify
Popular Examples
derivative of y=(6x^2+6x+4)/(sqrt(x))derivative of integral of (e^{\sqrt[3]{x}})/(x^{2/3)}tangent of f(x)=(3x)/(x+1),\at x=2tangent of derivative of (4x)/(x^2+1)derivative of x^3y^{''}-xy^'+y=0
Frequently Asked Questions (FAQ)
What is the derivative of xe^{(-x/2}) ?
The derivative of xe^{(-x/2}) is -(e^{-x/2}x)/2+e^{-x/2}What is the first derivative of xe^{(-x/2}) ?
The first derivative of xe^{(-x/2}) is -(e^{-x/2}x)/2+e^{-x/2}